2012
DOI: 10.1002/hyp.8382
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of the runoff processes in a remote montane cloud forest basin using Mixing Model Analysis and Mean Transit Time

Abstract: In this study, the Mean Transit Time and Mixing Model Analysis methods are combined to unravel the runoff generation process of the San Francisco River basin (73.5 km2) situated on the Amazonian side of the Cordillera Real in the southernmost Andes of Ecuador. The montane basin is covered with cloud forest, sub‐páramo, pasture and ferns. Nested sampling was applied for the collection of streamwater samples and discharge measurements in the main tributaries and outlet of the basin, and for the collection of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
64
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 68 publications
15
64
2
1
Order By: Relevance
“…They found that near-surface event water dominates runoff in these pristine rainforest-covered micro-catchments. In contrast, groundwater dominated fluxes tend to govern runoff generation on larger scales as revealed by geogenic tracer analyses (Bücker et al, 2010;Crespo et al, 2012). Surprisingly, Crespo et al (2012) derived MTTs of up to 260 to 350 days, despite the very responsive, flashy hydrographs that tend to react within a few hours to precipitation inputs.…”
Section: Windhorst Et Al: Impact Of Elevation and Weather Patternmentioning
confidence: 97%
See 1 more Smart Citation
“…They found that near-surface event water dominates runoff in these pristine rainforest-covered micro-catchments. In contrast, groundwater dominated fluxes tend to govern runoff generation on larger scales as revealed by geogenic tracer analyses (Bücker et al, 2010;Crespo et al, 2012). Surprisingly, Crespo et al (2012) derived MTTs of up to 260 to 350 days, despite the very responsive, flashy hydrographs that tend to react within a few hours to precipitation inputs.…”
Section: Windhorst Et Al: Impact Of Elevation and Weather Patternmentioning
confidence: 97%
“…In contrast, groundwater dominated fluxes tend to govern runoff generation on larger scales as revealed by geogenic tracer analyses (Bücker et al, 2010;Crespo et al, 2012). Surprisingly, Crespo et al (2012) derived MTTs of up to 260 to 350 days, despite the very responsive, flashy hydrographs that tend to react within a few hours to precipitation inputs. The uncertainty of this estimate remains unknown, given the limited information of stable isotopes in precipitation that the authors used.…”
Section: Windhorst Et Al: Impact Of Elevation and Weather Patternmentioning
confidence: 97%
“…This study is conducted in a 75 km 2 montane rain forest catchment in south Ecuador, the upper part of the Rio San Francisco, which has been under investigation since 2007 (Bogner et al, 2014;Boy et al, 2008;Bücker et al, 2011;Crespo et al, 2012;Fleischbein et al, 2006;Goller et al, 2005;Timbe et al, 2014;Windhorst et al, 2013b). The findings of those studies (briefly synthesized in Sect.…”
Section: Windhorst Et Al: Stable Water Isotope Tracing Through Hymentioning
confidence: 99%
“…Large shares of the soil water percolate to deeper horizons, thereby creating long mean transit times (MTT) (Crespo et al, 2012;Timbe et al, 2014). 4.…”
Section: Windhorst Et Al: Stable Water Isotope Tracing Through Hymentioning
confidence: 99%
“…The stream waters of the river and its tributaries are perennial and baseflow dominated. Previous research accounted the groundwater contribution in 85 % of the total runoff, characterized by MTTs on the order of 2 to 4 years (Timbe et al, 2014;Crespo et al, 2012). A detailed description of the physical, hydro- logical and land cover characteristics of the catchment and main tributaries are given in Timbe et al (2014), whereas additional information on the climate and ecosystem gradients of the research area can be found in Bendix et al (2008), Fiedler and Beck (2008) and Wilcke et al (2008).…”
Section: Study Areamentioning
confidence: 99%